Sistem Mutasi Guru SMK di Kota Manado Menggunakan Metode Fuzzy Simple Additive Weighting (F-SAW) - Eko Cristian Marthin; M. Aziz Muslim; M. Fauzan Edi Purnomo (Jurnal Rekayasa Elektrika, 2021)
Inter-school teacher exchange has a significant role in achieving good and equitable quality of education. This has become the focus of North Sulawesi’s regional education office, particularly in the city of Manado at the level of the vocational high School (SMK). Inter-school teacher exchange, which still works on the basis of Microsoft Excel manually, is an obstacle to transparent and objective decision-making. Decision Support Systems (DSS) can be a solution to these problems. In this study, the Fuzzy Simple Additive Weighing (F-SAW) method was used for a web-based DDS. This test is carried out on five sample data through calculations using Ms. Excel and the DSS system with the acquisition of  decision values of 0.91 and 0.93, respectively.